MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SEJARAH - Tri Hartoto (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2016)
This research aims to increase student activity so the impact on learning outcomes forstudents the history of class XII Science SMAN I Puggur in academic year 2015/2016. Theresearch method uses a class action (action research). GI cooperative learning canimprove the quality of teaching history. GI cooperative learning has a positive impact inimproving student achievement marked by increased mastery learning students in eachcycle, the first cycle (72.5%), the second cycle (80.0%), the third cycle (92.5%) , GIcooperative learning can make students feel themselves to get attention and theopportunity to express their opinions, ideas, ideas and questions.